Variations in microbial load of raw milk and influencing factors form dairy farms to collection centers of Esferayen area - A Jamshidi (Bihdāsht-i Mavādd-i Ghaz̠āyī, 2012)
Raw milk is among the highly perishable foods which are subjected to various environmental contaminations following milking. In this study, the factors influencing bacterial load of bulk-milk were investigated. For this purpose, 100 samples were obtained from dairy farms around Esferayen during spring, summer and autumn of 2009. The samples were taken in three stages: after milking, before transportation from dairy farm, and before delivering to milk-collection-center. The samples were analyzed for total bacteria count (TBC). To determine the factors which could influence the TBC of raw milk, a questionnaire sheet where designed. Statistical analysis were performed by means of logistic regression (genmod procedure), using SAS software (version 8.2). According to the results of this study, maintaining cold chain throughout the transportation and storage of raw milk, prevention of mastitis, cleaning and sanitizing of containers and equipments, age and breed of dairy cattle as well as indirect factors such as education level of dairy farmers, distance to milk-collection-center had significant effects (P